A review of counseling research using single‐case research design - Brown, Cian L.; Peltier, Corey; Smarinsky, Evan C.; Lewis, Olivia J.; Lee, David Y. (Journal of counseling and development, 2024)
Single‐case research designs (SCRDs) are a vital tool for researchers and practitioners in counseling to evaluate intervention and treatment effectiveness. This content analysis reviews the application of SCRDs in counseling to highlight knowledge accrued and existing gaps in the literature. We evaluated the methodological design and reporting adherence against recommended guidelines to provide guidance for future research. We included 50 SCRDs published between 2015 and 2021 across 15 journals (42 reviewed). Content results showed several trends, strengths, and areas of improvement in counseling SCRDs. No studies completely met the What Works Clearinghouse (2022) design standards or Single‐Case Reporting Guideline in Behavioural Interventions (SCRIBE) reporting standards, yet several indicators had high levels of adherence. We discuss how the experimental design process can be enhanced to improve the internal validity, ways to improve transparency in reporting SCRD results, and the importance of contextualizing SCRD methodology to the counseling field.